MR Imaging Findings in 2 Cases of Late Infantile GM1 Gangliosidosis - De Grandis, E.; Di Rocco, M.; Pessagno, A.; Veneselli, E.; Rossi, A. (American Journal of Neuroradiology, 2009)
SUMMARY: Late infantile GM1 gangliosidosis is a rare lysosomal disorder characterized by mental deterioration and progressive spastic, cerebellar, and extrapyramidal signs, without facial dysmorphisms and organomegaly. Neuroimaging findings have been reported in only a few cases. Here we report on predominant globus pallidus MR signal-intensity abnormalities in 2 patients with the late infantile form of GM1 gangliosidosis.